2020
DOI: 10.18332/ejm/124941
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress in Swedish midwives: A cross-sectional survey

Abstract: INTRODUCTION Midwives are exposed to emotional strain, which could affect their overall health. Lack of emotional well-being could be a reason for workforce attrition. The aim of the study was to investigate the prevalence of depressive symptoms, anxiety and stress among Swedish midwives in relation to background variables. METHODS A random sample of 1000 midwives were asked to participate and complete a questionnaire. Participants completed the Depression, Anxiety and Stress Scale, Copenhagen Burnout Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…The overall prevalence of Swedish midwives moderate/severe/very severe symptoms of depressive symptoms were (12%), anxiety (8.6%), and stress (7.2%) [36]. Midwives aged under 40 and less than 10 years of experience reported higher depressive symptoms, anxiety, and depression [36]. The studies mentioned above demonstrated the presence of psychological distress before the pandemic.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The overall prevalence of Swedish midwives moderate/severe/very severe symptoms of depressive symptoms were (12%), anxiety (8.6%), and stress (7.2%) [36]. Midwives aged under 40 and less than 10 years of experience reported higher depressive symptoms, anxiety, and depression [36]. The studies mentioned above demonstrated the presence of psychological distress before the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…In 2019, one-third of midwives in the United Kingdom reported moderate/severe/extreme levels of depression (33%), anxiety (38%), and stress (36.7%) [35]. The overall prevalence of Swedish midwives moderate/severe/very severe symptoms of depressive symptoms were (12%), anxiety (8.6%), and stress (7.2%) [36]. Midwives aged under 40 and less than 10 years of experience reported higher depressive symptoms, anxiety, and depression [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that there are scientific reports indicating the existence of a relationship between job seniority and the severity of anxiety or depression in midwives [24]. Båtsman et al (2020) point to a significant relationship between the occurrence of anxiety symptoms and professional experience -respondents with fewer than 10 years of overall work experience experienced greater severity of anxiety symptoms than midwives with greater work experience [24]. Therefore, it seems justified to take into account other factors related to the work setting that may reduce the severity of anxiety among midwives.…”
Section: Discussionmentioning
confidence: 99%
“…-praca zmianowa (nieregularne godziny pracy wpływają na rytm procesów fizjologicznych, które w konsekwencji mogą być źródłem wielu problemów zdrowotnych, takich jak zaburzenia snu, utrzymujące się zmęczenie, zaburzenia układu krążenia, problemy trawienne oraz zaburzenia poznawcze); -uciążliwe warunki pracy (częsty kontakt z zanieczyszczeniami, brudem, wydzielinami i drobnoustrojami chorobotwórczymi oraz wysiłek fizyczny związany z wykonywaniem czynności pielęgnacyjnych oraz asystą przy zabiegach); -obciążenie psychiczne (wysokie poczucie odpowiedzialności); -zbyt niskie zarobki; -zła współpraca (ze współpracownikami lub/i z pacjentami). Długotrwały stres może skutkować frustracją, brakiem energii, motywacji do pracy oraz przyczyniać się do rozwoju chorób przewlekłych (Mollart, Skinner, Newing, & Foureur, 2013;Båtsman, Fahlbeck, & Hildingsson, 2020). Jednak pomimo szeregu trudności i możliwości wystąpienia nieprzewidzianych sytuacji położne zgodnie z Ustawą o zawodach pielęgniarki i położnej zobowiązane są do wykonywania swojej pracy starannie oraz kompetentnie, zapewniając tym samym wysoką jakość opieki medycznej swoim pacjentom 6 .…”
Section: Stres Zawodowy W Pracy Położnejunclassified